THE TRADITION OF WRITING MUṢḤĀF AL-QUR'ĀN AKBĀR IN MUṢḤĀF AL-QUR'ĀN SCIENCES EDUCATION FOUNDATION (YPIIQ) WONOSOBO - Shofaussamawati Shofaussamawati; Zahro Firdausa Zahro Firdausa (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2020)
The aim of this article is to describe the writing of Muṣḥāf al-Qur'ān Sciences Education Foundation (YPIIQ) Wonosobo still written by hand in this sophisticated era. The type of this research uses the field research by a qualitative method approach which finds out the phenomenon and analyse the existing data. The process of collecting data uses interview, observation and documentation techniques, and it has found some interesting things. Firstly, the emergence of the tradition of writing Muṣḥāf by hand and giant size departing from KH. Muntaha's idea, he is the caretaker of the Al-Asy'ariyyah Taḥfῑż al-Qur’ān Islamic Boarding School, Kalibeber, Mojotengah, Wonosobo, Central of Java. The devotion of KH. Muntaha Al-Hafidz to al-Qur'ān made him to finally realise the grand Qur'ān writing project. KH. Muntaha al-Hafidz also wants to continue writing Al-Qur’ān that had been written by his grandfather, namely KH. Abdurrahim (1860-1916 AD). Secondly, before writing, there are certain provisions that must be carried out by writers namely they must be in a sacred condition when writing the muṣḥāf, do the sunnah prayers of two raka'at and write it accompanied by fasting except several days that are forbidden to fast. Thirdly, the strong factor that encourages the tradition of writing muṣḥāf at the Qur’ān Sciences Education Foundation (YPIIQ) Wonosobo is still being carried out till now because of devotion to teachers and wants to always glorify the muṣḥāf.